Izid rehabilitacijske obravnave bolnikov po ishemični možganski kapi v Splošni bolnišnici Nova Gorica - Černe, Katja (Rehabilitacija (Ljubljana), 2012)
Background: Stroke is the leading cause of people's functional impairment in developed countries, the functional outcome of patients however is determined also by the rehabilitation programme. In General Hospital Nova Gorica adults with stroke have the possibility to be included in a multidisciplinary rehabilitation programme at the Ward for handicapped youth immediately after the acute treatment period. The aim of this study was to evaluate the effect of multidisciplinary rehabilitation of patients after an ischemic stroke in our hospital. Methods: We enrolled 21 patients after ischemic stroke (9 men, 12 women) who underwent inpatient rehabilitation in our facility from January to June, 2010, in a prospective cohort study. We evaluated them at admission, at discharge and at the follow-up visit with the Functional Independence Measure (motor part - mFIM; cognitive part - cFIM) and the Berg Balance Scale, we performed the Mini Mental State Examination (MMSE), and in patients who were able to walk we measured the time they took for walking for 10 metres. Results: The mean age of the patients was 73.6 years (SD 11.3); they were admitted to the rehabilitation facility on average 15.9 days (SD 7.4) after stroke. The mean length of stay was 38.6 days (SD 22.8). The majority (81 %) of patients were discharged home. At discharge, we observed a significant improvement in mFIM (p < 0.001) and in the Berg Balance Scale score (p < 0.001) in comparison with admission. At the follow-up visit, which took place on average 121.1 days (SD 45.9) after discharge, we observed a significant improvement in mFIM (p = 0.001) and in the Berg Balance Scale score (p = 0,007) in comparison with discharge. The values of cFIM, MMSE and walking speed did not change significantly between admission, discharge and the follow-up visit. Conclusions: Efficacy of our rehabilitation program was confirmed regarding patients' motor functions and balance. We could not confirm the efficacy regarding walking speed or cognitive functions.
Keywords: cognitive functions; Executive Function; Gait; hoja; kognitivne funkcije; motor functions; motorične funkcije; možganska kap; Postural Balance; ravnotežje; rehabilitacija; rehabilitation; Stroke; vocational rehabilitation; walking ability; zmožnost hoje